Working Memory after Traumatic Brain Injury: The Neural Basis of Improved Performance with Methylphenidate - Manktelow, Anne E.; Menon, David K.; Sahakian, Barbara J.; Stamatakis, Emmanuel A. (Frontiers in Behavioral Neuroscience, 2017)
Traumatic brain injury (TBI) often results in cognitive impairments for patients. The aim of this proof of concept study was to establish the nature of abnormalities, in terms of activity and connectivity, in the working memory network of TBI patients and how these relate to compromised behavioural outcomes. Further, this study examined the neural correlates of working memory improvement following the administration of methylphenidate. We report behavioural, functional and structural MRI data from a group of 15 Healthy Controls (HC) and a group of 15 TBI patients, acquired during the execution of the N-back task. The patients were studied on two occasions after the administration of either placebo or 30 mg of methylphenidate. Between group tests revealed a significant difference in performance when HCs were compared to TBI patients on placebo (F(1,28)=4.426, p<0.05 ɳp2=0.136). This difference disappeared when the patients took methylphenidate (F(1,28)=3.665, p=0.66). Patients in the middle range of baseline performance demonstrated the most benefit from methylphenidate. Changes in the TBI patient activation levels in the Left Cerebellum significantly and positively correlated with changes in performance (r=0.509 df=13, p=0.05). Whole-brain connectivity analysis using the Left Cerebellum as a seed revealed widespread negative interactions between the Left Cerebellum and parietal and frontal cortices as well as subcortical areas. Neither the TBI group on methylphenidate nor the HC group demonstrated any significant negative interactions. Our findings indicate that a) TBI significantly reduces the levels of activation and connectivity strength between key areas of the working memory network and b) Methylphenidate improves the cognitive outcomes on a working memory task. Therefore we conclude that methylphenidate may render the working memory network in a TBI group more consistent with that of an intact working memory network.